The silver donkey - Hartnett, Sonya; Carlin, Laura (London : Walker Books, 2006)
In France during World War I, four French children learn about honesty, loyalty, and courage from an English army deserter who tells them a series of stories related to his small, silver donkey charm.
5.0
5-8.
5-8
Keywords: World War, 1914-1918 -- France -- Juvenile fiction; Conduct of life -- Fiction; Historical fiction; Soldiers -- Fiction; Storytelling -- Fiction; World War, 1914-1918 -- France -- Fiction; Conduct of life -- Fiction; Historical fiction; Soldiers -- Fiction; Storytelling -- Fiction; World War, 1914-1918 -- France -- Fiction; France -- History -- Fiction; France -- History -- Fiction